22.EVALUATING THE EFFECTIVENESS OF THE METHOD ONSET OF LABOR WITH PROPESS® IN PATIENTS WITH HIGH-RISK PREGNANCIES AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to Evaluation of the efficacy of Propess® on the onset of labor in patients with high-risk pregnancies at Nghe An Hospital of Obstetrics and Pediatrics in 2023. Subjects and methods: An observational study among 75 pregnant women with high-risk pregnancies and termination of pregnancy at Nghe An Hospital of Obstetrics and Pediatrics from 01/01/2024 to 30/09/2024.Results: The median age was 28.97 ± 4.79. The average Bishop score before KPCD is 2.37 ± 1.48. The failure rate when KPCD equals Propess® is 2.67%. The success rates of levels 1, 2 and 3 were 97.33%, 96% and 89.33%, respectively. There were 89.33% of successful vaginal deliveries and 10.67% of cases requiring cesarean section. In 48% of cases, oxytocin infusion is required after KPCD with Propess.Conclusion: There were 89.33% of successful vaginal deliveries and 10.67% of cases requiring cesarean section.
Keywords: high-risk pregnancy; vaginal delivery; cesarean section